ASSEMBLY DRAWINGS IN ENGINEERING TRAINING - Salieva Madina Adkhamzhanovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines the role of assembly drawings in the engineering training of students majoring in technical and oil and gas fields. It discusses the basic requirements for creating assembly drawings in accordance with the Unified System for Design Documentation (ESKD), their structure, content, and importance in the design, manufacture, and operation of machines and mechanisms. Particular attention is paid to the use of modern CAD systems in creating assembly drawings and developing the professional competencies of future engineers.